B7-H4 Pathway in Islet Transplantation and β-Cell Replacement Therapies. (9th August 2011) - Wang, Xiaojie; Hao, Jianqiang; Metzger, Daniel L.; Ao, Ziliang; Meloche, Mark; Verchere, C. Bruce; Chen, Lieping; Ou, Dawei; Mui, Alice; Warnock, Garth L.
Abstract : Type 1 diabetes (T1D) is a chronic autoimmune disease and characterized by absolute insulin deficiency. β -cell replacement by islet cell transplantation has been established as a feasible treatment option for T1D. The two main obstacles after islet transplantation are alloreactive T-cell-mediated graft rejection and recurrence of autoimmune diabetes mellitus in recipients. T cells play a central role in determining the outcome of both autoimmune responses and allograft survival. B7-H4, a newly identified B7 homolog, plays a key role in maintaining T-cell homeostasis by reducing T-cell proliferation and cytokine production. The relationship between B7-H4 and allograft survival/autoimmunity has been investigated recently in both islet transplantation and the nonobese diabetic (NOD) mouse models. B7-H4 protects allograft survival and generates donor-specific tolerance. It also prevents the development of autoimmune diabetes. More importantly, B7-H4 plays an indispensable role in alloimmunity in the absence of the classic CD28/CTLA-4 : B7 pathway, suggesting a synergistic/additive effect with other agents such as CTLA-4 on inhibition of unwanted immune responses.